Global prevalence of Eimeria species in goats: a systematic review and meta-analysis - Ali, Endris A.; Ghafar, Abdul; Angeles-Hernandez, Juan C.; Yaseen, Muhammad; Gauci, Charles G.; Beveridge, Ian; Baxendell, Sandra; Jabbar, Abdul (Frontiers in Veterinary Science, 2025)
BackgroundCoccidiosis is a protozoal disease caused by Eimeria species, the main symptom of which is diarrhea. Eimeria spp. infection can cause weight loss and ill-thrift in goats, and in severe cases, it can lead to mortality in kids, resulting in economic losses for the goat industry. This study aimed to determine the global prevalence of Eimeria spp. in goats and to identify the possible predictors of heterogeneity among selected studies.MethodsData were retrieved from five databases of major global importance (PubMed, Web of Science, CAB Direct, Scopus, and Google Scholar), with 255 studies published between 1963 and 2022 being included. A random-effects model was used to calculate pooled prevalence estimates with 95% confidence intervals (CI), followed by subgroup meta-analysis and meta-regression analysis to identify factors contributing to high prevalence and explore sources of heterogeneity among studies.ResultsThe estimated global prevalence of Eimeria spp. in goats was 62.9% (95% CI: 58.6–67.2). Our results indicated high inter-study variability (inconsistency index (I2) = 99.7%, p < 0.01). Among the variables analyzed, regions and quality of studies were the most significant predictors of heterogeneity. According to the region-based subgroup meta-analysis, North America had the highest estimated prevalence of Eimeria spp. (92.2, 95% CI: 82.7–98.2), followed by Europe (86.6, 95% CI: 79.8–92.3), while Asia had the lowest prevalence (52.0, 95% CI: 45.9–58.1). Most countries (n = 42/56) had an estimated prevalence above the overall pooled estimate (>62.9%). The subgroup of studies conducted in 2000 or later presented a lower prevalence of 59.6% (95% CI: 54.7–64.3). Studies with a score of 5–7 had a significantly higher prevalence (72.4, 95% CI: 66.2–78.2) than studies with low or medium scores (p < 0.01). The prevalence of Eimeria spp. in goats detected with conventional and molecular methods was 67.3% (95% CI: 47.0–84.7). Only 47% (119/255) of the studies provided details on identifying Eimeria at the species level. Overall, more than 26 Eimeria spp. have been identified in goats globally. Among these, the most frequently reported and pathogenic species were E. arloingi (115/119), E. ninakohlyakimovae (108/119), E. christenseni (94/119), and E. caprina (71/119). Other valid species that were reported less frequently include E. alijevi, E. hirci, E. caprovina, E. aspheronica and E. jolchijevi.ConclusionThese findings suggest that the pathogenic Eimeria spp. are widespread in goats globally. Given the high prevalence and the extensive distribution of pathogenic Eimeria spp. in goats, it is recommended that integrated parasite management approaches be implemented for the effective control of coccidiosis in goats.